A case report: deep and durable response to low-dose lenvatinib and tislelizumab in an elderly patient with advanced intrahepatic cholangiocarcinoma - Zhang, Pei; Wang, Xin; Li, Ruizhen; Li, Xiaoying; Cheng, Ke; Cao, Dan (Frontiers in Pharmacology, 2024)
Background: Older patients with advanced cholangiocarcinoma lack systemic therapy standards.These people have a high risk of chemotherapy, accompanied by adverse reactions and even discontinuation of treatment.Case presentation: We report a 78-year-old female with advanced intrahepatic cholangiocarcinoma presenting with unresectable lesions involving the hepatic veins, along with an extensive metastatic lymph nodes. After the geriatric assessment, capecitabine was utilized for only one cycle owing to adverse events (AEs). Next, a combination of low-dose lenvatinib and tislelizumab was administrated as a second-line treatment, which resulted in remarkable early tumor shrinkage. This following individual lenvatinib taper enabled a manageable safety profile and durable deep response. A nearcomplete response was achieved, with the primary tumor significantly reducing from 5.6 x 4.7 cm to nearly complete disappearance, accompanied by complete regression of lymph nodes, and both progression-free survival and overall survival exceeding 24 months.Conclusions: The case provide valuable insights that might could influence future treatment strategies for elderly patients with advanced cholangiocarcinoma, unsuitable for chemotherapy. The dose-individualized chemotherapy-free regime of lenvatinib and tislelizumab in this case, might be used in similar cases to improve their outcomes.Low dose, deep response, intrahepatic cholangiocarcinoma, elderly patient, case report